2015
DOI: 10.1097/brs.0000000000001057
|View full text |Cite
|
Sign up to set email alerts
|

Leriche-Like Syndrome as a Delayed Complication Following Posterior Instrumentation of a Traumatic L1 Fracture

Abstract: 5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…Currently, damage to the PGVs from pedicle screws in the thoracic vertebrae has been reported in several papers [2428], but this damage has rarely been reported in the lumbar vertebrae [18]. In 2010, Foxx et al [29] retrospectively analyzed 182 patients with thoracolumbar and lumbosacral pedicle screw fusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, damage to the PGVs from pedicle screws in the thoracic vertebrae has been reported in several papers [2428], but this damage has rarely been reported in the lumbar vertebrae [18]. In 2010, Foxx et al [29] retrospectively analyzed 182 patients with thoracolumbar and lumbosacral pedicle screw fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Zhuang et al [17] confirmed that the mechanical properties and early screw loosening of bone cement screws were not better than those of the BPSs. Because the abdominal aorta, inferior vena cava, and iliac vessels are located in front of the lumbar spine, a BPS that breaks through the anterior cortex of the lumbar vertebral body can potentially 0damage the prevertebral great vessels (PGVs) [18]. To the best of our knowledge, there have been no reports on the anatomy of the PGVs and their association with BPSs.…”
Section: Introductionmentioning
confidence: 99%
“…This was illustrated in a study done by Karami et al, where an increased fixation strength of bicortical screws was observed with screw toggle testing [12]. The drawback of a bicortical screw placement is the risk of iatrogenic damage to neurovascular structures anterior to the spine [32][33][34][35]. This leads to the question if the mechanical benefit of placing pedicle screws bicortically using a CBT justifies this associated risk.…”
Section: Discussionmentioning
confidence: 99%
“…[13] In the literature review, it was found that ALIF surgery at L2-L5 levels is most likely prone to cause vascular injury, [3][4][5] just as the procedure in our case. The explained reason is that left common iliac vessels normally transverse the prevertebral space the L4-5 interspace, and thus prevents direct access to the spine.…”
Section: Discussionmentioning
confidence: 99%